KADAR KLORIN PADA MIE SOHUN DI PASAR KEMANTRAN KABUPATEN TEGAL TAHUN 2018 - Wahyu Nusantara Putri; Tri Marthy Mulyasari (Poltekkes Kemenkes Semarang, 2019)
Sohun is a dry food product made from starch with a distinctive shape. In the process of making sohun using chlorine as a bleach agent and there are still chlorine remaining. The effects of chlorine in the short term cause ulcer disease and in the long term lead to liver and kidney cancer. The purpose of this research is to know the chlorine level in sohun noodle in Kemantran Traditional Market of Tegal Regency. The research method used with descriptive approach that aims to measure chlorine levels in sohun noodle in the Kemantran Traditional Market of Tegal Regency and to know the level of knowledge of sohun noodle traders with the number of samples of 5 traders of sohun noodle. The result of chlorine content in samples obtained 2 sohun noodles samples of positive using chlorine is sample B with chlorine level of 0.1 mg / L and sample C with chlorine level of 0.2 mg / L while the other 3 samples, were samples of sohun noodles A, D and E showed negative results using chlorine. And the knowledge level of sohun noodles traders in Kemantran Traditional Market of Tegal Regency is still bad. The research conclusion showed 2 samples of sohun noodles tested positive using chlorine and 3 samples of sohun noodles that were examined negatively using chlorine. Suggestions in cooperation with Tegal District Health Office to increase supervision on the use of Food Added Substances (BTP), especially in food industries and conduct guidance or counseling to existing traders in Kemantran Traditional Market of Tegal Regency about Food Added Substances (BTP) which allowed or not allowed by the government